2017
DOI: 10.1097/md.0000000000006703
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between prefrontal-striatal pathway impairment and cognitive impairment in patients with leukoaraiosis

Abstract: Our study aimed to investigate the changes of white matter microstructure of cortico-subcortical pathways using diffusion tensor imaging (DTI), and to explore the relationship between abnormal parameters of DTI and cognitive function underlying in patients with leukoaraiosis (LA).A total of 42 patients with LA and 42 age- and sex-matched healthy controls were recruited from Beijing Chaoyang Hospital, Capital Medical University between January 2012 and December 2012. All the subjects underwent scans of conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…White matter hyperintensities is the most common neuroimaging manifestation of CSVD, which is related to cognitive dysfunction or dementia. Studies that focused on NAWM have also confirmed that the change in DTI metrics of NAWM always precedes the development of WMH and is associated with MCI . Combined with the emergence of WMH penumbra theory, we propose that direct visual WMH may be a manifestation of more extensive and subtle WM microstructural degeneration and those changes of the properties in DTI may be the potential mechanism of WMH‐related MCI, as stated in the theory of cortical “disconnection” hypothesis .…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…White matter hyperintensities is the most common neuroimaging manifestation of CSVD, which is related to cognitive dysfunction or dementia. Studies that focused on NAWM have also confirmed that the change in DTI metrics of NAWM always precedes the development of WMH and is associated with MCI . Combined with the emergence of WMH penumbra theory, we propose that direct visual WMH may be a manifestation of more extensive and subtle WM microstructural degeneration and those changes of the properties in DTI may be the potential mechanism of WMH‐related MCI, as stated in the theory of cortical “disconnection” hypothesis .…”
Section: Discussionsupporting
confidence: 60%
“…Longitudinal follow‐up studies also showed further deterioration of cognitive function over time in WMH patients with mild cognitive impairment . Furthermore, loss of microstructural integrity of normal‐appearing white matter (NAWM) was associated with executive function, which further suggested that WMH might be an extreme case of continuous spectrum of white matter (WM) damage. White matter tract disruption in diffusion tensor imaging (DTI) may lead to disconnections among cortico‐cortical or cortico‐subcortical pathways vital for some cognitive function.…”
Section: Introductionmentioning
confidence: 96%
“…Indeed, our findings are supported by many previous neuroimaging studies. For example, microstructural WM disruption has been documented in ILA, such as the frontal WM tracts and corpus callosum (Yamauchi et al, 2000 ; Jokinen et al, 2007 ; Viana-Baptista et al, 2008 ; Wang et al, 2017 ). Moreover, resting-state functional MRI studies have also shown ILA-related alterations in functional connectivity (Chen et al, 2019 ; Liu et al, 2019a , b ).…”
Section: Discussionmentioning
confidence: 99%
“…We separately grouped the studies based on cross-sectional or longitudinal analysis. Studies on LA were entirely crosssectional [47,57,62] whereas studies related to VCI were predominantly longitudinal. Longitudinal studies [63,67,70,[78][79][80][81][83][84][85][86] focused on characterizing the disease progression using DTI measures.…”
Section: Diffusion Tensor Imaging (Dti)mentioning
confidence: 99%